The Effect of Stereotypical Barbaric Mobile Legends Streamers on Viewer Behavior: A Case Study of The Youtube Channel “Bang Pascol” - Rivaldy Maulana Putra; Khaerudin Imawan; Welly Wihayati (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
The rise of digital media, particularly YouTube, has given rise to new communication patterns that are widely embraced by the younger generation. Among Generation Z, the use of coarse or expressive language is often considered normal, especially in live-streamed gaming content that allows for direct interaction between streamers and viewers. This study aims to analyze how viewers interpret the Barbaric stereotype in live streams presented by Bang Pascol, both in digital communication and in everyday life. Using a qualitative case study approach through content observation, comment analysis, and interviews with Bang Pascol’s viewers and viewers of other streamers as a comparison, the results show that the Barbaric stereotype is interpreted in diverse ways. Some viewers accept it as entertainment and part of the streamer’s identity, while others are critical because this communication style can influence communication behavior, particularly among teenagers and children.